2017
DOI: 10.1007/s12011-017-0978-2
|View full text |Cite
|
Sign up to set email alerts
|

Hair Zinc and Severity of Symptoms Are Increased in Children with Attention Deficit and Hyperactivity Disorder: a Hair Multi-Element Profile Study

Abstract: Determination of bioelement levels in hair is an emerging non-invasive approach for screening bioelement deposition. However, the role of essential bioelement levels in hair and attention deficit/hyperactivity disorder (ADHD) risk or severity is largely unknown. In this study, we have compared multi-element hair profiles between healthy and ADHD Thai children. In addition, the correlations between bioelements and ADHD symptoms according to Diagnostic and Statistical Manual of Mental Disorders, 5th edition, dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Three studies were excluded due to unavailability of information regarding zinc levels 19 21 and two studies were excluded due to lack of reporting information in case and control groups separately and reporting the level of zinc in hemoglobin 22 , 23 . Finally, 22 articles were included in this meta-analysis, 14 studies assessed circulating levels of zinc 13 , 24 36 and 8 studies reported hair zinc levels 12 , 37 – 43 .
Figure 1 PRISMA flowchart describing the study’s systematic literature search and study selection.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies were excluded due to unavailability of information regarding zinc levels 19 21 and two studies were excluded due to lack of reporting information in case and control groups separately and reporting the level of zinc in hemoglobin 22 , 23 . Finally, 22 articles were included in this meta-analysis, 14 studies assessed circulating levels of zinc 13 , 24 36 and 8 studies reported hair zinc levels 12 , 37 – 43 .
Figure 1 PRISMA flowchart describing the study’s systematic literature search and study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…Except for one study 24 in which both case and control groups had diabetes, other studies used healthy individuals and people with ADHD as control and case groups, respectively. Of the available studies, four were conducted in Egypt 24 , 28 , 29 , 33 , three in Russia 13 , 37 , 38 , two in Turkey 32 , 36 , two in the United States 34 , 41 , and others in Syria 25 , China 26 , Iran 27 , Slovakia 30 , Israel 31 , Saudi Arabia 35 , New Zealand 39 , Indonesia 40 , Thailand 12 , Korea 42 , and Georgia 43 . Twenty studies had case–control design and only two studies 13 , 28 were conducted by cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children are not quite active and moody but only show moderate disorder in terms of function. Children are more susceptible to behavioral problems at the beginning and middle of childhood (13,17) . Parenting is a process of introducing and supporting a child's physical, emotional, social and intellectual development from a baby to an adult.. Another aspect is that parenting is the interaction between children and caregivers during care, including the process of developing appropriate knowledge and skills for children, ways to educate by giving rules and restrictions applied to their children, maintenance, instilling trust, how to get along, attitudes create an emotional atmosphere, protection and teach general behavior that can be accepted by society.…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin is a hormone secreted by the pineal glandule and is tasked with regulating the rhythm of the circadian cycle which is responsible for regulating the human sleep cycle. Children with emotional disorders often experience sleep disorders that are thought to be caused due to melatonin deficiency (17,29) . Zinc also acts as a precursor in the synthesis of tryptophan.…”
Section: Discussionmentioning
confidence: 99%